Semi-solvo thermal synthesis and characterization of zinc oxide nanostructures against food borne pathogens - JAYANT PAWAR,; MANISH SHINDE,; RAVINDRA CHAUDHARI,; E. A. SINGH, (International Journal of Pharma and Bio Sciences, 2017)
A global threat posed by foodborne pathogens can be rectified by the use of antimicrobial nanostructures. In this trajectory, ZnO nanomaterials are very important as they are biocompatible, cheap and easy to produce. The synthesis of ZnO nanostructures was carried out by facile semi-solvo thermal route using zinc acetate and urea as precursors mixed in 20 % ethylene glycol solvent at 1600 C for 24 hours. The structural and morphological analysis reveals formation of hexagonal ZnO nanostructures having flower like morphology. The antimicrobial activity against Bacillus cereus NCIM 5293 gram positive and Salmonella typhimurium NCIM 2501 gram negative model bacteria reveals their effective potential in food packaging applications. The MIC and MBC of ZnO nanomaterial was found to be 125µg/mL and 250µg/mL for Bacillus cereus and 250µg/mL as well as 500µg/mL for Salmonella typhimurium, respectively. Therefore, ZnO nanostructures can be used for the protection of assorted food products from the food pathogens.